Inter-state cross border superspreading event of SARS-CoV2 in Central India, May 2020 - Mathur, Mansi; Ramaswamy, Sudarshan; Sharma, Mitilesh; Dhuria, Meera; Arya, Sujata; Chauhan, Himanshu; Jain, S. K.; Singh, Sujeet Kumar (International Journal of Research in Medical Sciences, 2021)
Background: During the mid-weeks of May 2020, a superspreading event occurred in a town of Central India, where breaking bread together led to an outburst of COVID-19 cases. This led to a sudden increase of the daily average number of cases later on in the month. Methods: An epidemiological investigation was done to investigate the cause. Process of the epidemic investigation done has been described under three parts namely - Case finding, Contact tracing, Public health response. Results: Our epidemiological investigation and contact tracing of the index case confirmed a superspreading event of COVID-19 which occurred due to multiple social gatherings during mid weeks of May 2020. It was estimated that 118 cases belonged to G0 and 94 cases belonged to G1 generation of the index case. Conclusions: Most likely source of infection to the index case was from the guests who came for a social gathering on May 11, 2020 (lockdown 3) from a village across the border in Rajasthan, a high COVID-19 prevalent zone (Orange) to a low COVID-19 prevalent zone (Green).